Energy and Mineral Resources Mining Contradictions in Coal-Uranium Coexisting Basin and the Countermeasure Suggestions. Issue 1 (December 2020) - Wang, Wenxu; Wang, Wei; Yan, Pengbing; Zhao, Jinfeng
Abstract: It is common that sandstone-type uranium deposits co-exist with coal and oil & gas in the same sedimentary basin, and the output of uranium deposits is closely related to the coal seam or oil & gas reservoir. An "upper uranium and lower coal" ore-bearing pattern is formed in Ordos Basin and Erlian Basin in China. Due to the absence of unified resource mining plan and policy coordination mechanism, the coal-uranium resource mining contradictions have become increasingly prominent in coal-uranium coexisting areas in recent years. It is difficult to realize in-situ leaching exploitation of the coal-uranium resources in the Ordos coal-uranium coexisting area because of disorderly mineral resource mining, radioactive contamination risks are posed to the ambient environment of the mining area, and consequently, coal mine enterprises have to stop work and production, which gives rise to huge economic loss. Given this, the current resource contradictions in this area and their influence paths were comprehensively expounded through a systematic survey on a coal-uranium superposition area, and then the corresponding countermeasure suggestions were proposed.